Pengaruh Pengetahuan Awal Akuntansi, Kecerdasan Emosional Dan Efikasi Diri Terhadap Tingkat Pemahaman Akuntansi - Ainun Jariyah; Rochmawati Rochmawati (Jurnal Pendidikan Akuntansi (JPAK), 2020)
This study was conducted to examine and analyze the effect of prior knowledge of accounting, emotional intelligence and self-efficacy on the level of understanding of accounting in accounting education students, Faculty of Economics, State University of Surabaya. This research is a type of quantitative method. The research sample used is a saturated sampling technique with a total of 96 PAK undergraduate students departing 2017. Questionnaires (questionnaires) and documentation are techniques in collecting data. The results showed that initial accounting knowledge had a partial effect, emotional intelligence had no partial effect and self-efficacy had no partial effect. The results of the F test show that there is a simultaneous influence of initial accounting knowledge, emotional intelligence and self-efficacy on the level of accounting understanding in accounting education students, Faculty of Economics, Universitas Negeri Surabaya.